2014
DOI: 10.1021/jf503510h
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity in Vitro and in Vivo of Verbascose from Mung Beans (Phaseolus aureus)

Abstract: In the present study, the immunostimulatory activity of verbascose from mung beans (Phaseolus aureus) was evaluated by using in vitro cell models and in vivo animal models. The results of in vitro experiments showed that verbascose could enhance the ability of devouring neutral red of peritoneal macrophages and promote the release of nitric oxide and immune reactive molecules such as interleukin (IL)-6, IL-1β, interferon (IFN)-α, and IFN-γ. Treatment with verbascose at a dose of 200 μg/mL exhibited the best ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 55 publications
(72 reference statements)
0
32
0
1
Order By: Relevance
“…Serum haemolysin was evaluated using a previously described method with modification [40]. On the fifth and thirteenth day of GPMPP or vehicle administration, the control and experimental mice were immunized twice by intraperitoneal injection of 0.2 mL sheep erythrocyte suspension (SRBC, 2%, v / v ).…”
Section: Methodsmentioning
confidence: 99%
“…Serum haemolysin was evaluated using a previously described method with modification [40]. On the fifth and thirteenth day of GPMPP or vehicle administration, the control and experimental mice were immunized twice by intraperitoneal injection of 0.2 mL sheep erythrocyte suspension (SRBC, 2%, v / v ).…”
Section: Methodsmentioning
confidence: 99%
“…Polysaccharides isolated from the mung bean using water and alkali have been shown to activate macrophages [57,58]. Dai et al found that treatment with 200 μg/mL verbascose from the mung bean exhibited the most significant immunomodulatory activity in strengthening the ability of peritoneal macrophages to devour neutral red and promote the production of NO and immune reactive molecules (IL-1β, IL-6, interferon-α(IFN-α), and interferon-γ (IFN-γ) [73]. Furthermore, after administration of verbascose at a medium dose of 90 mg/kg body weight for 8 consecutive days, the index of the spleen, activity of lysozyme in spleen and serum, hemolysin level in serum, and swelling rate of earlap in the delayed type of hypersensitivity of immunosuppressed mice were significantly increased.…”
Section: Health Benefitsmentioning
confidence: 99%
“…Among the various oligosaccharides tested for potential prebiotic application, galactooligosaccharide (GOS), mainly found in animal milk (Boehm et al 2004;Martinez-Ferez et al 2006), is one of the functional oligosaccharides with high safety, wide acceptance and excellent feeding effect (Cardellecobas et al 2011). Moreover, a variety of beneficial health effects of GOS have been reported including modulating immune function and improving intestinal health (Dai et al 2014;Weaver et al 2011). In addition, much attention has been focused on growth regulating effects of GOS.…”
Section: Introductionmentioning
confidence: 99%